2007
DOI: 10.1158/1078-0432.ccr-06-2821
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Poly-l-Glutamate Camptothecin (CT-2106) Administered Weekly in Patients with Advanced Solid Malignancies

Abstract: Purpose: CT-2106 is a 20(S)-camptothecin poly-L-glutamate conjugate. This linkage stabilizes the active lactone form of camptothecin and enhances aqueous solubility. In addition, poly-Lglutamate is postulated to increase tumor delivery of the active compound through enhanced permeability and retention effect in tumor. We studied a weekly schedule of CT-2106 in patients with refractory solid tumor malignancies. Experimental Design: CT-2106 was infused (10 min i.v. infusion) on days 1, 8, and 15 of each 28-day c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…They are based on the traditional cytotoxic drugs (e.g. platinates [145,146], doxorubicin [147,148], camptothecin and analogues [149][150][151][152][153][154][155][156][157][158][159], paclitaxel/docetaxel [160][161][162][163][164], methotrexate [165], and irinotecan [166,167]). Xyotax (CT-2103 or OPAXIO), a PGA-paclitaxel conjugate, and NKTR-102, a polymer conjugate of irinotecan, are both currently in phase III clinical trials, being the conjugates closest to approval and market availability [164,[166][167][168].…”
Section: Polymer Therapeuticsmentioning
confidence: 99%
“…They are based on the traditional cytotoxic drugs (e.g. platinates [145,146], doxorubicin [147,148], camptothecin and analogues [149][150][151][152][153][154][155][156][157][158][159], paclitaxel/docetaxel [160][161][162][163][164], methotrexate [165], and irinotecan [166,167]). Xyotax (CT-2103 or OPAXIO), a PGA-paclitaxel conjugate, and NKTR-102, a polymer conjugate of irinotecan, are both currently in phase III clinical trials, being the conjugates closest to approval and market availability [164,[166][167][168].…”
Section: Polymer Therapeuticsmentioning
confidence: 99%
“…Four patients had stable disease (SD) for >9 weeks; 2 lung cancer patients (25 mg/m 2 ) had SD for >27 weeks. In a second Phase I trial in 26 patients, the MTD, toxicity, pharmacokinetics, and response rate of CT-21206 when administered weekly for 3 consecutive weeks of every 4-week cycle were determined [71]. With this schedule, the MTD was 75 mg/m 2 .…”
Section: Pg-gly-cpt (Ct-2106)mentioning
confidence: 99%
“…Although the study showed favourable pharmacokinetics and slower urinary excretion, no objective response (neither partial nor complete) was observed. 33 In 2006, CT-2106 entered phase II clinical trials for the second-line treatment of ovarian cancer. Primary endpoints were to measure response rate and secondary measurements were of toxicity, response duration, time to progression (TTP), and survival (ClinicalTrials.gov identifier NCT00291837).…”
Section: Polyamine Polymeric Nanoparticlesmentioning
confidence: 99%